Malmkjær, K., ?erban, A., & Louwagie, F. (Eds.). (2018). Key cultural texts in translation. John Benjamins. 320 pp. - Alfer, Alexa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Book review